Rough Living Surviving Violence and Homelessness - Robinson, Catherine (UTS Shopfront Series, 2010)
Rough Living: Surviving Violence and Homelessness reveals the ways in which intense chains of disadvantage, incorporating homelessness, are triggered by very early experiences of violence. Drawing on biographic interviews with six men and six women, the book bears witness not only to horrendous repeated experiences of physical and sexual violence, but discusses what may be understood as related multi-dimensional vulnerability in areas such as physical and mental health, education, employment and social connectedness. A picture of the long-term cycles of violent victimisation and homelessness, and their compounding traumatising effects, are made clear and the importance of trauma-informed service delivery is outlined as a key way forward.